(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
Our focus in this study revolves around investigating the following parabolic problem By using the Galerkin approximation and a family of potential wells, we obtain the existence of global solution and finite time blow-up under some suitable conditions. On the other hand, the results for asymptotic behavior of certain solutions with positive initial energy are also given.